Haemodynamic effects of a prehospital emergency anaesthesia protocol consisting of fentanyl, ketamine and rocuronium in patients with trauma: a retrospective analysis of data from a Helicopter Emergency Medical Service - Richard Lyon; Ewoud ter Avest; Dassen Ragavan; Joanne Griggs; Michael Dias; Sophie A Mitchinson (BMJ Open)
Objectives Prehospital rapid sequence induction (RSI) of anaesthesia is an intervention with significant associated risk. In this study, we aimed to investigate the haemodynamic response over time of a prehospital RSI protocol of fentanyl, ketamine and rocuronium in a heterogeneous population of trauma patients.Design, setting and participant We performed a retrospective study of all trauma patients who received a prehospital RSI for trauma by a physician staffed Helicopter Emergency Medical Service in the UK between 1 June 2018 and 1 February 2020.Primary outcome measure Primary outcome was defined as the incidence of clinically relevant hypotensive (systolic blood pressure (SBP) or mean arterial pressure (MAP) >20% below baseline, with an absolute SBP <90 mm Hg or MAP <65 mm Hg) or hypertensive (SBP or MAP >20% above baseline) episodes in the first 10 minutes post-RSI.Results In total, 322 patients were included. 204 patients (63%) received a full-dose induction of 3 μg/kg fentanyl, 2 mg/kg ketamine and 1 mg/kg rocuronium, whereas 128 patients (37%) received a reduced-dose induction. Blood pressures decreased on average 12 mm Hg (95% CI 7 to 16) in the full-dose group and 6 mm Hg (95% CI 1 to 11) in the reduced-dose group, p=0.10). A hypotensive episode (mean SBP drop 53 mm Hg) was noted in 29 patients: 17 (8.3%) receiving a full dose and 12 (10.2%) receiving a reduced-dose induction, p=0.69. The blood pressure nadir was recorded on average 6–8 min after RSI. A hypertensive episode was present in 22 patients (6.8%). The highest blood pressures were recorded in the first 3 min after RSI.Conclusion Prehospital induction of anaesthesia for trauma with fentanyl, ketamine and rocuronium is not related to a significant change in haemodynamics in most patients. However, a (delayed) hypotensive response with a significant drop in SBP should be anticipated in a minority of patients irrespective of the dose regimen chosen.